2015
DOI: 10.1007/s00394-015-0927-9
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean diet and academic performance in youth: the UP&DOWN study

Abstract: Adherence to the Mediterranean diet may have a beneficial influence on academic performance in youth. Importantly, the benefits of adherence to the Mediterranean diet on academic performance may be stronger as youth adhered to the optimal Mediterranean diet levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 34 publications
3
50
1
3
Order By: Relevance
“…Previous research has linked Mediterranean diet adherence to better academic performance of Mediterranean children [8, 36], and academic performance has been linked to self-esteem [24]. It is possible that the adolescents in the present sample had higher academic attainment which led to them more positively perceiving their school environment.…”
Section: Discussionmentioning
confidence: 80%
“…Previous research has linked Mediterranean diet adherence to better academic performance of Mediterranean children [8, 36], and academic performance has been linked to self-esteem [24]. It is possible that the adolescents in the present sample had higher academic attainment which led to them more positively perceiving their school environment.…”
Section: Discussionmentioning
confidence: 80%
“…For instance, diets with an excess of fat and sugar can lead to increased overweight indices and a negative belief about oneself [33,34]. Moreover, several studies have shown that a worse adherence to the MD is associated with lower academic performance and subsequent negative academic self-concept [35], and negative emotions, such as higher levels of stress and anxiety, and a subsequent negative emotional self-concept [36]. …”
Section: Introductionmentioning
confidence: 99%
“…Several authors [4,8] have used the KIDMED test to determine if subjects had good, average or poor adherence to the MedDiet. The results of this study agreed with those of other Spanish authors [5,15,71,72], who have demonstrated that about 50% of Spanish children and adolescents in other areas of Spain present good MedDiet adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The MedDiet pattern is represented by a diet pyramid characterized by common proportions of food consumption in the 16 countries around the Mediterranean Sea [7]. The typical MedDiet is characterised by high intakes of fruits, vegetables, pulses, whole grains (largely unrefined) cereals, tree nuts, as well as olive oil as the principal source of added fat, along with high to moderate intakes of fish and seafood, moderate consumption of eggs, poultry and dairy products (cheese and yoghurt), and low consumption of red meat [5,7,8,9]. This diet model, plays a preventive role in the development of cardiovascular and neurodegenerative diseases, certain cancers, diabetes and obesity [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation